HUBUNGAN ANTARA TINGKAT PENDIDIKAN, PENGETAHUAN, SIKAP DENGAN PERILAKU IBU BALITA DALAM PENCEGAHAN PENYAKIT DIARE DI PUSKESMAS BANCAK KABUPATEN SEMARANG - Dwi Retnaningsih, Mashuri, Arwani, (Jurnal Ilmu dan Teknologi Kesehatan, 2012)
RELATIONSHIP BETWEEN THE LEVEL OF EDUCATION, KNOWLEDGE, ATTITUDE WITH MOTHER BEHAVIOR OF CHILDREN IN DISEASE PREVENTION OF DIARRHEA IN HEALTH DISTRICT BANCAK SEMARANGDiarrheal disease is one of the main causes of deth of a toddler. Motherâtoddler has an important role in prevention of diarrheal disease. This reserdh using the methods of correlation with the approach of cross sectional, and withdrawal in a sample of sampling purposive is mother with toddlers the first, recorded in his visit to the health Bancak, and educated at least elementary. Research results with the Spearman Rank test shows that value of r is on the educated of 0,688 with a value of p = 0,000, r value for level of knowledge is 0,365 with the value of p = 0,000, and the value of r for attitude is 0,373 with the value of p = 0,000.There is a significant relationship with strong positive direction between levels of educated with the behavior of the motherâ toddler. There is a significant relationship with weak positive direction between levels of knowledge with the bahavior of motherâs toddler. There is a significant relationship with the positive directionis weak between attitude with the bahavior of motherâs toddler diarrhea disease prevention. The better the level of education, knowledge, attitude of motherâs toddler in prevention of diarrhea, it will be the better also their behavior in the prevention of diarrheal disease. Keywords :Education, Knowledge, Attitude and Behavior of Motherâs Toddler